Vortex behaviour under variable static pressure condition - Azman Hafiidz Aji, 1985-; Kahar Osman, supervisor; Includes bibliographical references (2008)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal )) - Universiti Teknologi Malaysia, 2008